New Directions in the Treatment of Progressive Forms of Multiple Sclerosis - Tuychiyeva Mokhinur Komilovna; Wasim Hazim (American Journal of Biomedicine and Pharmacy, 2025)
Progressive forms of multiple sclerosis (MS), including primary progressive MS (PPMS) and secondary progressive MS (SPMS), present significant treatment challenges due to their complex pathophysiology and limited responsiveness to conventional disease-modifying therapies (DMTs). This article explores the most recent advancements in the treatment of progressive MS, including emerging pharmacologic therapies, regenerative medicine, and personalized approaches. The development and application of monoclonal antibodies, autologous hematopoietic stem cell transplantation (AHSCT), remyelination-promoting agents, and precision medicine strategies are discussed in depth. Special emphasis is placed on ongoing clinical trials, the role of biomarkers in treatment selection, and the impact of new therapies on patient quality of life and long-term disease progression. The article also critically evaluates the limitations of existing therapeutic modalities and explores promising directions for future research. By synthesizing the latest clinical and translational findings, this review provides a comprehensive foundation for optimizing treatment strategies in patients with progressive MS.